Age-related decreases in relapses among adults with relapsing-onset multiple sclerosis. (October 2020) - Schwehr, Natalie A; Kuntz, Karen M; Butler, Mary; Enns, Eva A; Shippee, Nathan D; Kingwell, Elaine; Tremlett, Helen; Carpenter, Adam F; ,
Background: Relapsing-onset multiple sclerosis (MS) typically starts in early- to mid-adulthood, yet the trajectory of disease activity over the subsequent lifetime remains poorly defined. Previous studies have not quantified the age-specific portion of decreases in annualized relapse rates (ARR). Objective: The aim of this article is to determine, under a range of disease-related assumptions, the age-specific component of decreases in ARR over time among adults with relapsing-onset MS. Methods: We used a simulation modeling approach to examine a range of assumptions about changes in ARR due to age versus disability status. Scenarios included variations in initial ARR and rate of worsening on the Expanded Disability Status Scale. Model parameters were developed through analysis of MS patients in British Columbia, Canada, and literature review. Results: We found a substantial age-specific decrease in ARR in all simulated scenarios, independent of disability worsening. Under a range of clinically plausible assumptions, 88%–97% of the decrease was attributed to age and 3%–13% to disability. The age-specific decrease ranged from 22% to 37% per 5 years for a wide range of initial ARR (0.33–1.0). Conclusion: Decreases in ARR were due mostly to age rather than disability status. To facilitate informed decision making in MS, it is important to quantify the dynamic relationship between relapses and age.